Misbehavior detection and efficient revocation within VANET. (June 2019) - Hasrouny, Hamssa; Samhat, Abed Ellatif; Bassil, Carole; Laouiti, Anis
Abstract: Trustworthy communication in VANET Network is essential to provide functional, efficient and reliable traffic safety applications. The main concern arises on how to maintain only the trustworthy participants and revoke the misbehaving ones. In this paper, we propose a new framework for the certificate revocation process within VANET. This process can be activated by the Misbehavior Detection Systems (MDSs) running within vehicles and the Misbehavior Authority (MA) within the infrastructure, which identifies and excludes misbehaving vehicles to guarantee the long-term functionality of the network. These MDSs rely on the trust evaluation for participating vehicles which is updated continuously based on their behaviors. Therefore, the revocation is done periodically through geographical Certificate Revocation List (CRL) which specifies the certificates of all revoked vehicles within a specific area. This results in a lightweight solution for CRL management and distribution within a modular and secure infrastructure based on Public Key Infrastructure (PKI), group formation and trust evaluation. Simulation scenarios and risk analysis were carried out showing the advantages of the proposed revocation framework.